PENINGKATAN KOMPETENSI PEDAGOGIK DALAM MENYUSUN RPP MELALUI SUPERVISI AKADEMIK GURU SDN BULUH KUNING KECAMATAN SUNGAI DURIAN KABUPATEN KOTABARU - Syarwani Syarwani (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2023)
This study aims to improve the results and learning processes of Civics students in getting to know Pancasila values ​​and their implementation using the mind mapping cooperative learning model assisted by the inquiry approach. The results showed that in cycle I (one) which was completed individually out of 18 new students only there are 8 students 60% of whom meet the minimum completeness selection requirements (KKM) 70 or there are still students in the low category. Classically it has not been fulfilled because the average value obtained is 68%. Whereas in cycle II (two) classically it has been fulfilled, namely the average value obtained by students is 82.5% or is in the high category (complete). Keywords: Mind Mapping Cooperative Model Inquiry Approach; Citizenship Education; Pancasila Values ​​and Implementation.